PENILAIAN RANCANGAN KEMASAN BAKPIA BERBENTUK RANTANG MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Ika Atsari Dewi; Cahyo Wibowo; Sucipto Sucipto (Agroindustrial Technology, University of Trunojoyo Madura, 2019)
Bakpia is one food product that uses duplex cardboard as packaging material. Buying bakpia both in a small or big amount of packages need secondary packaging such as plastic bags and cardboards. “Rantang”-shaped packaging is designed to get practical, enviromental friendly, and attractive packaging. The objective of this research is to find out the importance level of customer attribute (Whats) against “rantang”-shaped packaging and to find out the technical responses that must be carried out by a manufacturer in order the packaging design is accepted by consumers. QFD method is used to find out consumers’ needs and desires as well as to systematically evaluate packaging capabilities sampled from 30 respondents. QFD method comprises of 7 phases, namely, collecting consumer voice, organizing House of Quality (HoQ), creating technical response, determining the technical response relationship to consumer needs, determining technical relations, benchmarking, and target. Results show the highest scores for importance level of consumer attribute go to packaging shape and packaging design with Importance to customer score of 4,67 dan 4,43 which are above average. Manufacturers should pay more attention to visual packaging design, packaging convenience while carrying, practical, varius number of stack, maximum limit of stack, appropriate cardboard, and precise packaging size as technical responses.